Preliminary Assessment on Autecological Studies of Beardless Barb, Cyclocheilichthys apogon (Valenciennes, 1842) from Muda Reservoir of Kedah, Malaysia - Nor Aziella Mohd Rosli; Khaironizam Md Zain (Tropical Life Sciences Research, 2016)
Like many other countries, reservoirs in Malaysia are primarily built for various functions such as hydroelectric power generation, drinking water supply, flood mitigation and irrigation for agricultural purposes. Artisanal fisheries activities were also performed in these reservoirs. The freshwater fish are a requisite source of protein for the rural population. Consequently, the fish resources in reservoirs should be carefully maintained at sustainable level. Present study elucidates the preliminary assessment on autecological studies of beardless barb, Cyclocheilichthys apogon as a model of fish biota in Muda Reservoir. This research investigates the growth pattern of C. apogon using length-weight relationship and their condition factor. A total of 307 specimens were captured using cast net for six consecutive months from March 2014 until August 2014. The growth coefficient (b) from the length-weight equation (W = aLb) for male and female of C. apogon were 3.150 and 3.185, respectively, indicating positive allometric growth. The condition factor values of male and female of C. apogon were 1.023 ± 0.111 and 1.026 ± 0.100, respectively, suggesting that C. apogon is in good condition in Muda Reservoir. The paucity of research on the autecological study in the Muda Reservoir contributes to the main reason of performing this research. The findings will serve as baseline information of this species in Muda Reservoir, as well as for comparative study in the future.